Adult Participation in Evening Secondary Schools: The Findings of Empirical Research in the Greek Islands - Papadimitriou, Achilleas (INSTED: Interdisciplinary Studies in Education & Society, 2023)
The study of adult participation in education and the examination of the factors that influence their final decision is one of the most critical issues in the field. This article summarises the findings of empirical research on adult engagement in evening schools in Greece, with an emphasis on evening schools in the Greek islands. Evening schools started in Greece around 60 years ago. These schools, now part of the secondary education system, are primarily aimed towards those who work during the day (mostly adults). Their goal is to provide the opportunity for adults who, for some reason, interrupted their studies in Gymnasium (lower secondary/middle school) or Lyceum (upper secondary/high school) to complete it. There has never been a study on residents of Greek islands who participate in educational programmes of this nature. The presented research investigates factors that impact adult participation in all evening schools administratively situated in Greek islands. Between February and May 2022, 268 adult students participated in the study by completing a survey questionnaire that was quantitatively evaluated using SPSSs. The sample comes from all the islands where evening Lyceums operate. To determine the elements that influence participation, the data was submitted to component analysis using the Principal Component Analysis (PCA) approach. Four of the discovered factors are deemed critical (self-assessment, attitudes towards education, educational perspective and expectations), while others seem somewhat relevant and have a role.